2012
DOI: 10.1111/j.1463-1318.2012.03108.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family history of gastric cancer on colorectal neoplasias in young Japanese

Abstract: In the young population under 50 years of age, a family history of gastric cancer is an independent risk factor for the development of colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However, because the prevalence of CRC in this study was extremely low (0.1%), no relationship between GC FH and CRC was seen. Similarly, though a Japanese study that included 300 young adults aged <50 years reported that a FH of GC was an independent risk factor for CRN 15 . However, this did not assess the association between GC FH and CRC risk because the number of patients with CRC was only 4 (1.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the prevalence of CRC in this study was extremely low (0.1%), no relationship between GC FH and CRC was seen. Similarly, though a Japanese study that included 300 young adults aged <50 years reported that a FH of GC was an independent risk factor for CRN 15 . However, this did not assess the association between GC FH and CRC risk because the number of patients with CRC was only 4 (1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two studies revealed that a FH of GC was a risk factor for colorectal neoplasia (CRN) 14,15 . However, the proportion of CRC among CRN in these two reports was extremely low, and both showed that a FH of GC was associated with an increased risk of colorectal adenoma, a precursor of CRC 14,15 . Whether a FH of GC is related to the risk of CRC and whether an FH of CRC is related to the risk of GC or gastric adenoma, a precancerous lesion of GC, remains ill defined.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also investigated upper gastrointestinal disorders as the clinical covariables for presence of early colon cancer. It has been well known that patients with gastric cancer frequently show synchronous or metachronous colon cancers, 47–49 and colon cancer and CD have been also reported to be the predictors of the presence of Barrett’s esophagus and reflux esophagitis 30 . On the other hand, Helicobacter pylori infection has showed an inverse correlation with the presence of CD 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Kupelian et al ( 15 ) reported that prostate cancer patients with a family history of prostate carcinoma show worse clinical outcomes. Hata et al ( 16 ) reported that a family history of gastric cancer is a risk factor for colorectal neoplasia. Minami et al ( 17 ) reported that a family history of gastric cancer increases mortality in gastric cancer patients under 60 years old.…”
Section: Discussionmentioning
confidence: 99%